The effect of thiol functional groups on bovine serum albumin/chitosan buccal mucoadhesive patches - ALARÇİN, EMİNE (My University, 2022)
In this research, the effect of thiol functional groups on bovine serum albumin (BSA)/chitosan (Chi) based buccal mucoadhesive patch was investigated. Thiolated BSA (BSA-SH) was prepared via 2-mercaptoethanol. FTIR and H-1 NMR results confirmed that BSA-SH was synthesized successfully. The buccal mucoadhesive patches were fabricated by the solvent casting method. Following the structural characterization of BSA/Chi and BSA-SH/Chi buccal patches, the mechanical characterization was performed by tensile tests. The drug release from triamcinolone acetonide (TR) loaded buccal patches was evaluated in-vitro in simulated salivary. According to the ex-vivo buccal adhesion experiments, the mechanical and mucoadhesion properties of BSA-SH/Chi buccal patch had improved compared to BSA/Chi buccal patch. The total cumulative TR permeated after 12 h was higher for BSASH/Chi than BSA/Chi buccal patches. The developed mucoadhesive buccal patches were found to be biocompatible in vitro. To conclude, the thiolated BSA-SH/Chi buccal adhesive patch is a promising biomaterial for a satisfied drug delivery, which provides advantages for various oral applications.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides